Evaluation of combination therapy with peeling added to minimal invasive blepharoplasty in lower eyelid rejuvenation. (3rd April 2020) - Asilian, Ali; Shahmoradi, Zabihollah; Talakoub, Mahboobeh; Mokhtari, Fatemeh; Siadat, Amir Hossein; Mohaghegh, Fatemeh; Adibi, Neda; Mozafarpoor, Samaneh; Kazemipour, Samira; Danesh, Farzaneh; Hafezi, Hossein
Abstract: Introduction: Aging is an inevitable process in life that can pose unsatisfactory changes in appearance. Recently, rejuvenation surgeries have opened an exciting new window toward people who are vulnerable according to their facial appearance. Periocular plastic microsurgeries are among the most common aesthetic surgeries with various outcomes. The current study was aimed to compare outcomes of blepharoplasty with and without peeling regarding lower eyelid rejuvenation. Methods: This is a randomized clinical trial study conducted on 30‐patients referred for inferior lid rejuvenation in 2017‐18. Patients were randomly divided into two 15‐member subgroups of microinvasive blepharoplasty with and without peeling. Peeling for the group underwent blepharopeeling was performed all over the inferior periocular region using Phenol 89%. Then, skin and underlying muscle were incised superficially, and underlying fat tissue was excised. The other group underwent blepharoplasty without peeling. Patients were followed daily for 2 months to assess complications, patients' and physicians' satisfaction. Results: Two assessed groups were not statistically different regarding age and gender distribution ( P ‐value = .417 and .666, respectively). Considering patients' opinion, symmetry, scar formation, skin laxity, swelling, and total satisfaction score were not different between two groups ( P ‐value > .05) while physicians presented similar outcomes except for better scar formation status of peeling add‐on therapy ( P ‐value = .042). Rate of adverse effects was significantly higher among those under blepharoplasty plus peeling treatment ( P ‐value < .05). Conclusion: Outcomes of blepharoplasty alone versus blepharoplasty plus peeling were not significantly different regarding both patients' and physicians' assessments in general while fewer complications due to blepharoplasty without peeling were presented.